Osteomyelitis associated with Bartonella henselae infection in a young cat. Issue 2 (September 2022) - Hui, Jamie; Ryan, Kirk A; Rademacher, Nathalie; Neupane, Pradeep; Breitschwerdt, Edward B
Case summary: A 1-year-old male intact domestic shorthair cat was evaluated for acute onset non-weightbearing left forelimb lameness and generalized peripheral lymphadenopathy. CT identified a monostotic aggressive bone lesion with an incomplete fracture of the left radial metaphysis. Bone aspirates yielded osteoblasts with minimal nuclear atypia. Abdominal ultrasound revealed a nodular spleen and lymphadenopathy; cytologically, both contained lymphoid hyperplasia. A urine histoplasma antigen test was negative. Bartonella henselae and Mycoplasma haemominutum DNA was amplified by PCR from peripheral blood. Indirect immunofluorescence documented strong B henselae immunoreactivity, with lower Bartonella vinsonii subspecies berkhoffii and Bartonella koehlerae antibody titers. After the administration of doxycycline and pradofloxacin for suspected Bartonella -induced osteomyelitis, lameness resolved rapidly. Six-week post-treatment radiographs identified healing of the affected bone, and Bartonella species enrichment blood culture was negative. B henselae antibody titers decreased four-fold over a year, supporting seroreversion. Relevance and novel information: B henselae is a flea-transmitted, host-adapted species, not previously implicated as a cause of osteomyelitis in cats. B henselae subclinical bacteremia is highly prevalent among cats; however, bacteremia has been associated with lymphadenopathy and febrile illness in cats. This report describes a unique clinical presentation in association with B henselae infection in a cat.